Task-switching and frontal cortex functioning across adulthood: An fNIRS study - Michael K. Yeung (NeuroImage)
Switching between tasks is slower and more error-prone than performing a single task. While studies have compared task-switching and associated neural processing between younger and older adults, knowledge of age-related differences in components of task-switching across adulthood, and associated neural mechanisms, remains elusive. In this study, these age differences were investigated using functional near-infrared spectroscopy (fNIRS). A sample of 132 adults aged 18–79 undertook a variant of the Trail Making Test and a task-switching paradigm. Hemodynamic changes in the bilateral frontal cortex during the task-switching paradigm were measured using a 48-channel fNIRS device. Behavioral results showed that age showed a negative linear relationship with time taken to task-switch and a negative quadratic relationship with success in task-switching. In addition, fNIRS results showed that age had a positive linear relationship with activation in the left posterolateral frontal cortex across trial conditions. Among older adults, who had slower and less accurate switch performance than younger adults, greater left posterolateral frontal activation was associated with faster and more accurate switch performance. Therefore, different aspects of task-switching performance exhibit varying patterns of age-related differences across adulthood. Increased engagement of the left posterolateral frontal cortex, which plays a specific role in reconfiguring and implementing relevant task rules, may help older adults compensate for declined switch performance.